Educação e saúde: entendendo a dengue através da elaboração de podcasts como material (in)formativo - Cunha, Lorena Ribeiro (2023)
Dengue fever is the most prevalent arbovirosis in subtropical and tropical countries, including Brazil, where the environment is suitable for the growth and multiplication of the mosquito that transmits the disease, the Aedes aegypti. It is a reemerging endemic illness that has become a significant public health issue as well as a social and environmental concern. Throughout the most restrictive period of the Covid-19 pandemic, in which the main concern became the new coronavirus, dengue manifested itself silently. In 2022, there were reports of outbreaks in localities in Minas Gerais in a short period of time. Given this scenario, it is essential to present circumstances that can inspire educators, students, and members of the community to change their attitudes toward the illness. With the technological advancement and the incorporation of digital media in the teaching-learning processes, we can observe the increasing use of the podcast tool, a digital media in mp3 format, similar to radio programs, that can be heard in any place and environment. This dissertation describes the creation and validation of a (in)formative material in podcast format that offers reflections on health and environmental education, approaches dengue fever in a lighthearted manner, and the various contents associated with the spread of epidemics, including the etiological agent, the immune response, prophylactic measures, and reflections on individual and collective attitudes for elementary school teachers and students. The podcast narratives were inspired by reports of interviews with three teachers and the tabulated results of questionnaires administered to a group of elementary school teachers. The five episodes of the collection called “Dengue Cast” were published in the “Anchor” application. After listening to the podcast, teachers were sent a survey via Google Forms to complete in order to validate the (in)formative materials. According to the findings, 80% of teachers would use the material in the classroom, while 20% might not because it does not fit into their students' realities due to the need for technological devices.